Effect of lactobacilli inoculation on protein and carbohydrate fractions, ensiling characteristics and bacterial community of alfalfa silage - Huo, Wenjie; Zhang, Yujuan; Zhang, Luyao; Shen, Chen; Chen, Lei; Liu, Qiang; Zhang, Shuanlin; Wang, Cong; Guo, Gang (Frontiers in Microbiology, 2022)
Introduction Alfalfa (Medicago sativa L.) silage is one of the major forages with high protein for ruminants. Methods The objective of this study was to investigate the effects of lactobacilli inoculants on protein and carbohydrate fractions, ensiling characteristics and bacterial community of alfalfa silage. Wilted alfalfa (35% dry matter) was inoculated without (control) or with Lactobacillus coryniformis, Lactobacillus casei, Lactobacillus plantarum, and Lactobacillus pentosus and ensiled for 7, 15, and 60 days. Results and discussion Silage inoculated with L. pentosus was superior to L. coryniformis, L. casei, L. plantarum in improving the fermentation quality of alfalfa silage, as indicated by the lowest ammonia nitrogen content and silage pH during ensiling. There was minor difference in water soluble carbohydrates content among all silages, but L. pentosus inoculants was more efficient at using xylose to produce lactic acid, with lower xylose content and higher lactic acid content than the other inoculants. Compared with the control, L. pentosus inoculants did not affect true protein content of silage, but increased the proportions of buffer soluble protein and acid detergent soluble protein. The L. pentosus inoculants reduced the bacterial diversity In alfalfa silage with lower Shannon, Chao1, and Ace indices, and promoted relative abundance of lactobacillus and decreased the relative abundance of Pediococcus compared with the control. As well as L. pentosus inoculants up-regulated amino acid, carbohydrate, energy, terpenoids, and polypeptides metabolism, and promoted lactic acid fermentation process. In summary, the fermentation quality and nutrient preservation of alfalfa silage were efficiently improved by inoculated with L. pentosus.